Quantitative analysis of PBBs and PBDEs in plastic parts of electrical and electronics equipment according to RoHS regulation by gas chromatography/mass spectrometry - Sittidech, Manop; Panyawathanakit, Nathalamon (Bulletin of Applied Sciences, 2022)
A test method has been developed in this research for quantitative analysis of polybrominated biphenyls (PBBs) and polybrominated diphenyl ethers (PBDEs) in various plastics, including acrylonitrilebutadiene–styrene, polypropylene, polyethylene, high-impact polystyrene and polyethylene terephthalate plastics based on the solvent extraction of the sample with soxhlet extraction technique and detection by gas chromatography/mass spectrometry. It was found that the test method was able to quantitate monobrominated- decabrominated biphenyl and monobrominated diphenyl ether–nonabrominated diphenyl ether between 100-1,750 mg/kg and decabrominated diphenyl ether between 100–8,000 mg/kg. The limit of detection (LOD) was between 3.9-25.5mg/kg. The limit of quantitation (LOQ) was between 13.1-85.0 mg/kg. The precision of the method expressed as percentage relative standard deviation was between 1.8 and 10.2, except 17.0 for BB-209 at lowest concentration (100 mg/kg). The accuracy of the method expressed as percentage recovery was between 80.9 and 116.8, except 130.1 for BDE-047 at lowest concentration (100 mg/kg). The obtained accuracy and precision of the method therefore meet the required accuracy expressed as % recovery which is between 70-130% and the required precision expressed as percentage relative standard deviation which is less than 20%RSD of the IEC 62321:2008 international standard method.